The reform process of the railway sector in Europe: A disaggregated regulatory approach - Günter Knieps; Patrick Zenhäusern (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2011)
The railroad package of 2001 focusing on access regulation is in the process of a reform. Particularly, the European Commission intends to remove the obstacles to fair competition that have been identified since 2001. In this context, the paper points out the relevance of the disaggregated regulatory approach. It is necessary to differentiate between infrastructure components which are monopolistic bottlenecks (e.g. railway tracks) and competitive components (e. g. service functions like ticketing). Competition on the markets for railway transport services requires non-discriminatory access to the railway infrastructures. As well the horizontal interoperability between national railway networks is a prerequisite that full competition on European markets for railway services can evolve. Train access charges should provide incentives for the different track companies to participate in collaborations offering international cross-border based track capacities, whereas a regulatory prescription of international track corridors conflicts with the competence to allocate the track capacities of the different track companies. Finally, the complex question of the interplay between discrimination and the deficit problem is addressed in order to present solutions to avoid crosssubsidization between track infrastructure and markets for transport services and to guarantee the efficient usage of public funds.
Keywords: 330